2009
DOI: 10.3109/14767050903029576
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular access deviceversusventriculosubgaleal shunt in post hemorrhagic hydrocephalus associated with prematurity

Abstract: VSGS is an effective means of providing temporary continuous drainage of CSF in PHH with an acceptable complication rate. VSGS has many advantages that make it superior to VAD as a temporizing shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 10 publications
1
12
0
3
Order By: Relevance
“…Our result is concordant with data in the literature [2, 17, 18] in which the PHH rate varies between 20 and 35%. Risk factors for PHH were high IVH grade and increased HC at diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Our result is concordant with data in the literature [2, 17, 18] in which the PHH rate varies between 20 and 35%. Risk factors for PHH were high IVH grade and increased HC at diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…There have been several retrospective reports from single institutions, and one from multiple institutions, that describe perioperative complications and the need for conversion to a permanent shunt. 54,57 A recent retrospective study reported the use of both devices at a single institution; the choice of device was based on the surgeon’s preference. 57 The mean age of the infants at the time of surgery was similar in the 2 treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…VSGSs are often appealing because they obviate the need for placing hardware that is notorious for its infection risk. Many groups have identified complications with this procedure [4,20,21,22,23]. Limbrick et al [4] looked at a series of 325 Papile grade III and IV premature infants and found 95 who required a temporizing procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Lam and Heilman [23] specifically compared their series of 32 preterm infants with IVH and divided them into two groups, one treated with VAD and one with VSGS. In this small series, patients treated with a VSGS had similar rates of avoiding placement of a permanent shunt (28.57%) while VAD patients were more frequently shunted (only 6.25% avoiding shunt placement).…”
Section: Discussionmentioning
confidence: 99%